2014
DOI: 10.3390/ijms151222214
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Polarity in the Evolution of the K+ Binding Site of Pyruvate Kinase

Abstract: In a previous phylogenetic study of the family of pyruvate kinase, we found one cluster with Glu117 and another with Lys117. Those sequences with Glu117 have Thr113 and are K+-dependent, whereas those with Lys117 have Leu113 and are K+-independent. The carbonyl oxygen of Thr113 is one of the residues that coordinate K+ in the active site. Even though the side chain of Thr113 does not participate in binding K+, the strict co-evolution between position 117 and 113 suggests that T113 may be the result of the evol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…The kinetic parameters for the activation of Vc IPK by K + , NH 4 + , Rb + and Cs + are shown in Table 1 , but kinetic parameters for Na + and Li + could not to be calculated, because the lack of saturation to include in Table 1 . In comparison with other K + -dependent PKs, Vc IPK exhibited higher k cat and 2 to 5-fold lower K 0.5 for the monovalent cations [ 34 , 40 ]. According to [ 41 , 42 ], VCIPK is a good example of Type Ib activation by monovalent cations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The kinetic parameters for the activation of Vc IPK by K + , NH 4 + , Rb + and Cs + are shown in Table 1 , but kinetic parameters for Na + and Li + could not to be calculated, because the lack of saturation to include in Table 1 . In comparison with other K + -dependent PKs, Vc IPK exhibited higher k cat and 2 to 5-fold lower K 0.5 for the monovalent cations [ 34 , 40 ]. According to [ 41 , 42 ], VCIPK is a good example of Type Ib activation by monovalent cations.…”
Section: Resultsmentioning
confidence: 99%
“…In comparison with other K + -dependent PKs, Vc IPK exhibited higher k cat and 2 to 5-fold lower K 0.5 for the monovalent cations [34, 40]. According to [41,42], VCIPK is a good example of Type Ib activation by monovalent cations.…”
Section: Resultsmentioning
confidence: 99%
“…It is important to note that the activation curves of WT-RMPK with Na + and Li + did saturate (see Table 1). In previous studies, WT-RMPK activation exhibited no saturation of these cations at an ionic strength of 223 mM ionic strength maintained with HEPES [21]. (CH 3 ) 4 N + may bind to non-specific sites of the enzyme favoring Na + and Li + occupation of the monovalent binding site.…”
Section: Resultsmentioning
confidence: 81%
“…In contrast, ion selectivity of T113L was altered; maximal activation followed the order Rb + > NH 4 + > K + > Cs + . It was found that the polarity of residue 113 is determinant in the partition of K + into its site [21]. E117K (Figure 4B), T113L/E117K (Figure 4C), and T113L/K114Q/E117K mutants (Figure 4D) were K + -independent.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation